2006
DOI: 10.1002/jbt.20133
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing expression of α1C calcium L-type channel subunit mRNA in rat ventricular myocytes upon manganese exposure

Abstract: Manganese is an essential trace element found in many enzymes. As it is the case of many essential trace elements, excessive level of manganese is toxic. It has been proven that excessive manganese could cause heart problems. In order to understand the mechanism of manganese toxicity in the heart, the effects of manganese on isolated rat ventricular myocytes were studied. The L-type calcium channel current was measured by whole-cell patch clamp recording mode. In the electrophysiology experiments, both 50 micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 30 publications
1
15
0
1
Order By: Relevance
“…On the other hand, other results point to the toxic action of high levels of manganese which are manifested in sinus tachycardia, brachycardia, arrhythmia, sinister megacardia, and accelerated heart-beat (11). These outcomes are associated with manganese interaction with the L-type calcium channel in the cardiovascular system (34). Our ECG results show that shortterm, high-dose treatment with MnCl 2 did not cause any serious disturbances except for slightly shortened QT and RR intervals.…”
Section: Discussionmentioning
confidence: 63%
“…On the other hand, other results point to the toxic action of high levels of manganese which are manifested in sinus tachycardia, brachycardia, arrhythmia, sinister megacardia, and accelerated heart-beat (11). These outcomes are associated with manganese interaction with the L-type calcium channel in the cardiovascular system (34). Our ECG results show that shortterm, high-dose treatment with MnCl 2 did not cause any serious disturbances except for slightly shortened QT and RR intervals.…”
Section: Discussionmentioning
confidence: 63%
“…The animal study's ethics and animal care was approved by the institution. Single rat ventricular myocytes were obtained by an enzymatic dissociation technique (Yang et al 2006). The Sprague-Dawley rat (either sex, weighing 150-180g) was sacrificed, and the heart was quickly excised and placed in oxygenated cold (4 • C) Ca 2+ -free MOPS solution.…”
Section: Preparation Of Ventricular Myocytesmentioning
confidence: 99%
“…In manganese exposed workers, disturbed autonomic nervous function and changing of cardiac rhythm as well as blood pressure have been observed (Barrington et al 1998). The in vitro studies showed that manganese could block the L-type calcium channel and reduce the heart rate; at the same time the heart retained a high content of manganese and calcium (Brurok et al 1997a;1997b;Yang et al 2006). Manganese is also capable of restraining the function of proton pump and reducing mitochondrial membrane potential, resulting in injury to myocardial cells (Jiang and Zheng 2005).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Manganese could affect neuromuscular transmission by interaction with the mitochondrial calcium uniporter and disturbing the ion balance in muscle membranes [11]. In vitro studies also showed that manganese could block the L-type calcium channels in the heart and reduce the heart rate, in addition to inducing an imbalance of the ions, with retention of high contents of manganese and calcium [12][13][14][15]. Manganese was also capable of restraining the function of the proton pump and reducing the mitochondrial membrane potential, resulting in injury to myocardial cells [7].…”
Section: Introductionmentioning
confidence: 99%